Influence of neodymium substitution on structural, magnetic and spectroscopic properties of Ni–Zn–Al nano-ferrites. Issue 22 (8th April 2021) - Amri, N.; Massoudi, J.; Nouri, K.; Triki, M.; Dhahri, E.; Bessais, L.
Abstract : The incorporation of Nd 3+ in the Ni–Zn–Al ferrite spinel causes an improvement in magnetic parameters. Spectroscopic properties were discussed based on FTIR and Raman measurements and proved the purity and good crystallization of the samples. Abstract : Ni0.6 Zn0.4 Al0.5 Fe1.5− x Nd x O4 ferrite samples, with x = 0.00, 0.05, 0.075 and 0.1, were synthesized using the sol–gel method. The effects of Nd 3+ doping on the structural, magnetic and spectroscopic properties were investigated. XRD Rietveld refinement carried out using the FULLPROF program shows that the Ni–Zn ferrite retains its pure single phase cubic structure with Fd 3̄ m space group. An increase in lattice constant and porosity happens with increasing Nd 3+ concentration. FTIR spectra present the two prominent absorption bands in the range of 400 to 600 cm −1 which are the fingerprint region of all ferrites. The change in Raman modes in the synthesized ferrite system were observed with Nd 3+ substitution. The magnetization curves show a typical transition, at the Curie temperature T C, from a low temperature ferrimagnetic state to a high temperature paramagnetic state. The saturation magnetization, coercivity and remanence magnetization are found to be decreasing with increasing the Nd 3+ concentration.